2000
DOI: 10.1002/1099-1395(200101)14:1<11::aid-poc329>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexation of ?-cyclodextrin and 6-O-?-�maltosyl- and 2-O-(2-hydroxypropyl)-?-cyclodextrins �with some fluorescent dyes

Abstract: Spectrofluorimetric titrations were performed in aqueous phosphate buffer (pH 7.20, 0.1 mol dm−3) to determine the binding constants of β‐cyclodextrin (1), mono(6‐O‐α‐maltosyl)‐β‐cyclodextrin (2) and mono[2‐O‐(2‐hydroxypropyl)]‐β‐cyclodextrin (3) with four fluorescent dyes, ammonium 8‐anilino‐1‐naphthalenesulfonate (ANS), sodium 2‐(p‐toluidino)naphthalene‐6‐sulfonate (TNS), Acridine Red (AR) and Rhodamine B (RhB). The fluorescence of ANS, TNS and AR were enhanced, whereas that of RhB was quenched, by the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…These phenomena suggested that the fluorophore experienced a less polar environment and the inclusion complex was formed by adding host compound. On the other hand, the bridged bis(β-cyclodextrin)s 3 − 5 with long spacers would quench the fluorescence of RhB, which is consistent with the case of β-cyclodextrin or modified β-cyclodextrins . It is unexpected that the bis(β-cyclodextrin) 2 tethered by a shorter linker effectively enhanced the original fluorescence intensity of RhB.…”
Section: Resultssupporting
confidence: 77%
“…These phenomena suggested that the fluorophore experienced a less polar environment and the inclusion complex was formed by adding host compound. On the other hand, the bridged bis(β-cyclodextrin)s 3 − 5 with long spacers would quench the fluorescence of RhB, which is consistent with the case of β-cyclodextrin or modified β-cyclodextrins . It is unexpected that the bis(β-cyclodextrin) 2 tethered by a shorter linker effectively enhanced the original fluorescence intensity of RhB.…”
Section: Resultssupporting
confidence: 77%
“…However, there are some literature reports of such a phenomenon, although the reasons for the fluorescence quenching are not always very clear. Schuette et al have explained the reduction in the fluorescence of acridine dye in the presence of β-CD in terms of increased intersystem crossing of acridine in the relatively aprotic medium inside the β-CD cavity . Liu et al have attributed the fluorescence quenching of rhodamine B in the presence of β-CD to the preferential complexation of β-CD with the nonfluorescent lactone form of rhodamine B and a conversion of some fluorescent zwitterionic form of the dye to the nonfluorescent lactone form in the presence of β-CD . Very recently, Zhou et al have reported the fluorescence quenching of RF in the presence of CB7, although no explanation was provided for the observed effect .…”
Section: Resultsmentioning
confidence: 99%
“…The lifetimes of aniline (2.7 ns) and N ‐methylaniline (3.7 ns) in the presence of β ‐cyclodextrin are consistent with the above long lifetime. On the other hand, the inclusion complex stabilities of aniline ( K S =61 dm 3 mol −1 ) and N ‐methylaniline ( K S =83 dm 3 mol −1 ) with β ‐cyclodextrin are also in accord with that of ANS 35…”
Section: Resultsmentioning
confidence: 76%